2014
DOI: 10.1159/000366278
|View full text |Cite
|
Sign up to set email alerts
|

Airway Wall Remodeling in Young and Adult Rats with Experimentally Provoked Bronchial Asthma

Abstract: Background: Airway wall remodeling is a typical finding in patients suffering from bronchial asthma. While morphological changes have been thoroughly described in adults, less is known about such changes in children because of the limited accessibility of relevant material. To overcome this constraint, animal asthma models may be used instead of human specimens. This study examined rats with artificially stimulated chronic asthma-like symptoms. Methods: Brown Norway rats of two age categories (young and adult)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Airway remodeling in asthma, a complex event, is characterized by several features such as subepithelial fibrosis, airway inflammation, smooth-muscle hyperplasia, mucous-gland hypertrophy, goblet cell metaplasia and angiogenesis [30,31]. However, the relations between these various phenotypes are not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Airway remodeling in asthma, a complex event, is characterized by several features such as subepithelial fibrosis, airway inflammation, smooth-muscle hyperplasia, mucous-gland hypertrophy, goblet cell metaplasia and angiogenesis [30,31]. However, the relations between these various phenotypes are not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological changes in the lung and bronchial tissues were observed and images were captured using a BX-60 microscope (Olympus, Tokyo, Japan). The tissues were scored based on the presence of inflammatory cells, using the following scale: Absent (0), rare ( 1 ), mild ( 2 ), moderate ( 3 ) or severe ( 4 ). Scoring was performed by an observer in a blinded-manner.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Consistent with the increase in markers of airway eosinophilia in human neonates, 6 rodent models of airway inflammation have shown that airway eosinophilia is increased in neonates. [7][8][9] However, despite increased eosinophilia at a young age, changes in airway structural cells are more severe later in life. 7,9 Leukocytes, which infiltrate the respiratory tissue of allergic and asthmatic patients, produce cytokines, such as IL-4, IL-13, IL-5 and TGF-b1, which promote inflammation and remodeling.…”
mentioning
confidence: 99%
“…[7][8][9] However, despite increased eosinophilia at a young age, changes in airway structural cells are more severe later in life. 7,9 Leukocytes, which infiltrate the respiratory tissue of allergic and asthmatic patients, produce cytokines, such as IL-4, IL-13, IL-5 and TGF-b1, which promote inflammation and remodeling. 10 In addition, myeloid cells produce lipid mediators, such as leukotrienes (LTs), which perpetuate inflammatory cell recruitment and remodeling.…”
mentioning
confidence: 99%